A randomized, double blind, placebo controlled study of spirulina supplementation on indices of mental and physical fatigue in men. (17th February 2016) - Johnson, Morgan; Hassinger, Lauren; Davis, Joshua; Devor, Steven T.; DiSilvestro, Robert A.
Abstract: Spirulina may increase people's ability to resist mental and physical fatigue. This study tested that hypothesis in a randomized, double blinded, placebo controlled study in men. After 1 week, a 3 g/day dose of spirulina produced a small, but statistically significant increase in exercise output (Kcals consumed in 30 min exercise on a cross trainer machine). A mathematical based mental fatigue test showed improved performance 4 h after the first time of supplementation as well as 8 weeks later. Similarly, a subjective survey for a sense of physical and mental fatigue showed improvement within 4 h of the first supplementation as well as 8 weeks later. These results show that spirulina intake can affect fatigue in men.